Proposta de sistema microcontrolado para aquisição de dados e automação de ambientes residenciais - Silva Filho, Sandoval Santos (2018)
The Residential Automation allows the insertion of technology inside the residences, so as to allow remote or local control of the di erent equipments of a residence, besides bringing bene ts to its occupants. However, many existing systems still have high deployment costs and are dedicated to a single function, such as security or convenience. In this way, this research seeks to improve the existing Residential Automation Systems through the integration of residential appliances, allowing them to have di erent requirements such as security, convenience and energy e ciency in a single application, aiming at the lower redundancy of the electronic devices present in the user's home. In addition, there was a concern to use more popular technologies, such as Raspberry Pi, an expansion card and a mobile device with the Android platform, in order to provide a system with lower cost. Through an exploratory research in which researches were carried out in books and articles, in order to understand the context of Residential Automation and the most used technologies, a prototype was developed that allows the user, remotely, to control the lighting and sound environment, manage the alarm, view the temperature and humidity, and monitor a camera installed in the residential environment. In addition, the system o ers greater security in the residence by allowing the monitoring of the leakage of LPG and smoke. The tests and results obtained with the development of the project indicated that the use of Raspberry Pi in Automation Systems is quite feasible as well as the integration with mobile devices that use the Android platform